Propuesta técnica y económica para la creación de una planta procesadora de semielaborados de cacao en el cantón la Troncal provincia del Cañar, año 2014 - Robles Álvarez, William Johnny (2015)
The research on the development of an economic technical proposal for a plant processing semi-finished products based on cocoa was made in the canton The Trunk province of Cañar in 2014. The specific objectives of this research were to prepare an assessment of consumption of semi-finished cocoa products locally, nationally and internationally, a technical study for the establishment of the company, determine the placement and location of the plant, design the layout and technical organization, conduct economic and financial study for the creation of semi-processing plant cocoa. The investigation concluded essentially that the proposed technique shows economic returns. The project has an internal rate of return of 35%, the NPV reached: $ 4,222,574.99, and the benefit-cost ratio yielded results in a value of 1.09, all these indicators show the economic viability of the project Regarding the technical study, the research showed that the basic process for processing semi-finished products made with cocoa contains the following sections: - Treating cocoa Section - Section ground cocoa liquor - Blocking section cocoa liquor - Section pressed - Section filtering cocoa butter - Blocking section cocoa butter - Section pulverized The plant will have an installed capacity of 6,000 tons a year (which gives 750 kg of cocoa beans per hour) based on the following schedule: Capacity: 6000 ton / year (18 tons / day) Working hours: 8000 per year. Fat Percentage: 50-54% in grains Fat Percentage: 10-12% after the process The investment of equipment and machinery for the processing plant cocoa semi-finished products amounted to $ 7,400,796.72 and the value in infrastructure (physical works) to a value of $ 321,820.00, resulting in a total investment for this project to $ 7,722,616.72.